The Influence of Discipline and Motivation in Improving Employee Performance in LJ Dua Brothers Fish Cracker Factory Employees - Pratama, Putra Fajar; Robbie, Iqbal; Arifiani, Ratya Shafira; Sa'diyah, Chalimatuz (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This research aims to determine the influence of discipline and motivation on the performance of LJ Dua Bersaudara cracker factory employees. The sample in this study was 40 employees. The sampling technique for this research uses saturated sampling. The type of research used is survey research with a quantitative approach. The data collection technique used was a questionnaire. Data analysis used multiple linear regression. The research results found that motivation had a significant effect on employee performance, discipline had no significant effect on employee performance, and motivation was the variable that had the most influence on the performance of employees at the LJ Dua Bersaudara cracker factory.